2014
DOI: 10.1007/s12253-014-9815-5
|View full text |Cite
|
Sign up to set email alerts
|

Pathologic Complete Remission after Preoperative High-Dose-Rate Brachytherapy in Patients with Operable Cervical Cancer: Preliminary Results of a Prospective Randomized Multicenter Study

Abstract: The role of preoperative intrauterine brachytherapy (BT) in the multidisciplinary treatment of early stage cervical carcinoma (ESCC) is controversial. In 2005, a prospective randomized multicenter study was initiated in Hungary in order to explore the potential advantages of preoperative high-dose-rate (HDR) BT. In this article we evaluate the efficiency of preoperative HDR BT by the rate of pathologic complete remission (pCR) in the first 185 patients enrolled in the study at the National Institute of Oncolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 21 publications
2
18
1
Order By: Relevance
“…However, in several retrospective studies, neoadjuvant brachytherapy and chemotherapy followed by RS for stage IB2 and IIA cervical cancer patients had no obvious inferiority to NACT + RS [31,32]. Additionally, Vízkeleti et al observed that the postoperative response rate in patients who received preoperative intrauterine brachytherapy was higher than that in patients who received RS alone (P = 0.03), and the rate of positive surgical margins was significantly lower (P = 0.02) [33]. This suggests that the underlying reason for our results is that radiotherapy and neoadjuvant brachytherapy reduce the pathological response in cervical AC.…”
Section: Discussionmentioning
confidence: 99%
“…However, in several retrospective studies, neoadjuvant brachytherapy and chemotherapy followed by RS for stage IB2 and IIA cervical cancer patients had no obvious inferiority to NACT + RS [31,32]. Additionally, Vízkeleti et al observed that the postoperative response rate in patients who received preoperative intrauterine brachytherapy was higher than that in patients who received RS alone (P = 0.03), and the rate of positive surgical margins was significantly lower (P = 0.02) [33]. This suggests that the underlying reason for our results is that radiotherapy and neoadjuvant brachytherapy reduce the pathological response in cervical AC.…”
Section: Discussionmentioning
confidence: 99%
“…However, the National Comprehensive Cancer Network guidelines only recommend primary surgery followed by radiotherapy, depending on the prognostic factors detected in the surgical specimen 4. Nevertheless, image-guided brachytherapy is effective for delivering high radiation doses to cervical cancer tumors while limiting the dose delivered to organs at risk, and available retrospective data suggest that pre-operative brachytherapy is a safe and effective treatment 6–11. Therefore, this study aimed to describe the experience at our academic center, where early stage cervical cancer is treated using pre-operative brachytherapy followed by Wertheim-type hysterectomy, and to determine which patients might benefit from this strategy.…”
Section: Introductionmentioning
confidence: 99%
“…Their results suggest that preoperative radiotherapy does not improve postoperative pathology. J. Vízkeleti et al [16] conducted a prospective study between 2005 and 2010. Fifty patients were retrospectively included in the PR and SD groups.…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that preoperative radiotherapy significantly increased the rate of pathological complete remission. J. Vízkeleti, G. Frhlich, S. Varga, [10] and C. Polg ar et al conducted a prospective multicentre study in 2005. Their results showed that postoperative pathological complete remission was significantly higher in the PR group than in the SD group (25.7% vs 11.4%), while there was no significant difference in local tumour control (LTC), distant metastasis-free survival (DMFS) or overall survival (OS) between the two arms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation